Doświadczenie refleksyjne w codzienności edukacyjnej – spojrzenie pragmatystyczne - Paszenda, Iwona (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2017)
In the first part of the article the author presents main principles of pragmatism by referring to the literature on this subject. In the second part she decodes, points out and describes selected thoughts of the prominent philosopher and educator – John Dewey, which relate to the issue of reflective experience and thinking in daily education. The theses proposed by the representative of pragmatistic philosophy, recalled in the article, may be a source of instruction and inspiration for modern pedagogy providing a theoretical base for creating alternative models of education and upbringing.
Keywords: education; John Dewey; pragmatism; reflective experience; thinking